Identification of a Differentiation Factor of Indonesian Ongole Cattle Breeds Based on Microsatellite Markers and Mitochondrial DNA - Paskah Partogi Agung; Alfandy Hermansyah (Buletin Peternakan, 2018)
This study was conducted to identify the differentiation factor of Indonesian Ongole cattle breeds (Sumba Ongole and Ongole Grade) based on the 12 microsatellite markers and Cyt b gene polymorphism. A total of 50 blood samples (25 samples for each cattle breed) were used in this study. The multiplex DNA fragment analysis was conducted for allele identification based on the microsatellite markers. The haplotype identification (based on the mitochondrial DNA) was conducted using restriction fragment length polymorphism (RFLP) analysis with three restriction enzymes i.e. HinfI, HaeIII, and XbaI. Twelve microsatellite loci in this study revealed high polymorphism. A total of 82 alleles were detected in the SO cattle and 117 alleles were detected in the PO cattle. The TGLA227 and ETH225 were specific locus candidates which are different in the size and the number of alleles in the SO and PO cattle breeds. The B (HinfI), D (HaeIII), and Y (XbaI) haplotypes were found only in the PO cattle breed samples. The X haplotype was found in all samples of the SO cattle breed but was not found in all samples of the PO cattle breed. The Y haplotype was found in all samples of the PO cattle breed but was not found in all samples of the SO cattle breed. It can be concluded that the TGLA227 and ETH225 (based on microsatellite markers) and the B, D, X, and Y haplotypes (based on the mitochondrial DNA) can be considered as the differentiation factors between the SO and PO cattle breeds.